Estimation of Distance of Euler`s Broken Line From Constant Multitude - M. S. Gabrielyan (National Academy of Sciences of Armenia)
The sharp estimation of distance of Euler`s broken line which is built by extremal strategy relative to maximal stable bridge for any terminal time interval is determined. Определяется достаточно точная оценка расстояния ломаной Эйлера, построенной экстремальной стратегией относительно максимального стабильного моста для любого конечного промежутка времени
Keywords: Physics